2007
DOI: 10.1021/jp073539t
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Aqueous Thermochemistry:  Application to the Oxidation of Hydroxylamine in Nitric Acid Solution

Abstract: Ab initio molecular orbital calculations were performed and thermochemical parameters estimated for 46 species involved in the oxidation of hydroxylamine in aqueous nitric acid solution. Solution-phase properties were estimated using the several levels of theory in Gaussian03 and using COSMOtherm. The use of computational chemistry calculations for the estimation of physical properties and constants in solution is addressed. The connection between the pseudochemical potential of Ben-Naim and the traditional st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 42 publications
4
64
1
Order By: Relevance
“…We have benchmarked the accuracy that can be achieved by different level of theory separately for the three parts. The findings for the benchmark systems and the example shown in the previous section are in accordance with recent studies on reaction energies and activation energies . It can be concluded that a well‐chosen combination of DFT and high level WFT for the gas phase and thermodynamic energy contribution with COSMO‐RS calculated free energy of solvations can yield ΔGsoln and within an error range of 10 kJ/mol.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…We have benchmarked the accuracy that can be achieved by different level of theory separately for the three parts. The findings for the benchmark systems and the example shown in the previous section are in accordance with recent studies on reaction energies and activation energies . It can be concluded that a well‐chosen combination of DFT and high level WFT for the gas phase and thermodynamic energy contribution with COSMO‐RS calculated free energy of solvations can yield ΔGsoln and within an error range of 10 kJ/mol.…”
Section: Resultssupporting
confidence: 89%
“…The findings for the benchmark systems and the example shown in the previous section are in accordance with recent studies on reaction energies and activation energies. 81,[84][85][86][87][88][89] It can be concluded that a well-chosen combination of DFT and high level WFT for the gas phase and thermodynamic energy contribution with COSMO-RS calculated free energy of solvations can yield DG soln and within an error range of 10 kJ/mol. An even better prediction quality drawing close to "chemical" accuracy < 5 kJ/mol, can be achieved if no major rearrangements of the molecules geometric and electronic structures occur during the course of the reaction, as in the hydrogenation example presented above.…”
Section: Resultsmentioning
confidence: 92%
“…These factors can be accounted for by using the implicit COSMO‐RS solvation model . For example, Green et al employed this approach to investigate the autocatalytic oxidation of hydroxylamine in nitric acid solutions and analyze differences between calculated and experimentally obtained energy functions (Δ G , Δ H , Δ S ) …”
Section: Introductionmentioning
confidence: 99%
“…[34,35] For example, Green et al employed this approach to investigate the autocatalytic oxidation of hydroxylamine in nitric acid solutions and analyze differences between calculated and experimentally obtained energy functions (ΔG, ΔH, ΔS). [36] In this work, we employ a composite DFT-COSMO-RS scheme to carry out a rapid and detailed analysis of conditiondependencies of the thermodynamic parameters in complex multicomponent reactive solutions. As a showcase, we focus on a model homogeneous catalytic reaction that is the basepromoted CO 2 reduction to formates catalyzed by homogeneous Ru pincer catalysts ( Figure 1a).…”
Section: Introductionmentioning
confidence: 99%
“…Various reliable models of gas‐phase reactions have been proposed to date, all of which work to explain observed combustion behaviors . More recently, models for the liquid‐phase reactions of energetic salts have also been developed . However, there are no detailed reaction models for the condensed phase reactions of AN, only semidetailed mechanisms .…”
Section: Introductionmentioning
confidence: 99%